PRINCIPLES OF DESIGNING WELL SEPARATORS - Feodorov, A.B.; Afanasov, V.I.; Gaevsky, V.N.; Dunaeva, S.P.; Miroshnikov, R.S.; Kondrashov, P.M. (Journal of Applied Engineering Science, 2018)
Vortex motion is effectively used in the development of wellbore filter designs. Further development of the principles of such design requires the development of some principles based on experimental observations and computer modeling. A constructive analogy between the wellbore filter and the Ranque vortex tube is shown. The results of experimental and theoretical studies of the vortex tube are applied as a basis for designing a well separator. Recommendations are formulated regarding the radius of the inner branch pipe of the downhole filter placed in the body. Approaches are discussed when choosing the length of the working section of the well separator, as well as the choice of the shape of the input cochlear, the size of the outlet diaphragm, and the shape of the sand suspension window.